Efek Corporate Social Responsibility pada Brand Equity Dimediasi Corporate Image dan Brand Awareness - Rulloh Delia Anggorawati; Budiyanto Budiyanto; Esti Margiyanti Utami (Business Management Analysis Journal (BMAJ), 2021)
The purpose of this study examine the influence of corporate social responsibility on brand equity; the effect of corporate social responsibility on brand awareness; the influence of corporate social responsibility on corporate image; the influence of brand awareness on brand equity; the effect of corporate image on brand equity; effect of corporate social responsibility on brand equity mediated by brand awareness; effect of corporate social responsibility on brand equity mediated by corporate image. Sample of this research is 120 people. Sampling technique used in this study is judgment sampling. Hypothesis testing used hierarchical regression analysis. The results showed that corporate social responsibility has an positive effect on brand equity, corporate social responsibility has a positive effect on brand awareness, corporate social responsibility has a positive effect on corporate image, brand awareness has a positive effect on brand equity, corporate image has a positive effect on brand equity, brand awareness mediates the effect of corporate social responsibility on brand equity, and corporate image mediates the influence of  corporate social responsibility on brand equity.Penelitian ini bertujuan untuk menguji pengaruh corporate social responsibility terhadap brand equity; pengaruh corporate social responsibility terhadap brand awareness; pengaruh corporate social responsibility terhadap corporate image; pengaruh brand awareness terhadap brand equity; pengaruh corporate image terhadap brand equity; pengaruh corporate social responsibility terhadap brand equity yang dimediasi oleh brand awareness; pengaruh corporate social responsibility terhadap brand equity yang dimediasi oleh corporate image. Sampel penelitian ini berjumlah 120 orang. Teknik sampling yang digunakan dalam penelitian ini yaitu judgement sampling. Pengujian hipotesis yang digunakan adalah hierarchical regression analysis. Hasil penelitian menunjukkan bahwa corporate social responsibility berpengaruh positif terhadap brand equity, corporate social responsibility berpengaruh positif terhadap brand awareness, corporate social responsibility berpengaruh positif terhadap corporate image, brand awareness berpengaruh positif terhadap brand equity, corporateimage berpengaruh positif terhadap brand equity, brand awareness memediasi pengaruh corporate social responsibility terhadap brand equity, dan corporate image memediasi pengaruh corporate social responsibility terhadap brand equity.